6(2x/3)=2(4x/7)

Simple and best practice solution for 6(2x/3)=2(4x/7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x/3)=2(4x/7) equation:



6(2x/3)=2(4x/7)
We move all terms to the left:
6(2x/3)-(2(4x/7))=0
We add all the numbers together, and all the variables
6(+2x/3)-(2(+4x/7))=0
We multiply parentheses
12x-(2(+4x/7))=0
We multiply all the terms by the denominator
12x*7))-(2(+4x=0
We add all the numbers together, and all the variables
4x+12x*7))-(2(=0
Wy multiply elements
84x^2+4x=0
a = 84; b = 4; c = 0;
Δ = b2-4ac
Δ = 42-4·84·0
Δ = 16
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{16}=4$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(4)-4}{2*84}=\frac{-8}{168} =-1/21 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(4)+4}{2*84}=\frac{0}{168} =0 $

See similar equations:

| 75+x/5=35 | | 5w+3=w-9 | | -2+4x=5(20x+22)-x | | 5x^2-12=166 | | 5=y/2.56+3 | | 2(x^2+4)=12 | | -4(y+3)=-4 | | 2(x+5)-(x-2)=-3(x-3) | | -4(w+9)=-6w-32 | | 3/7=n/4.2 | | -14+3x=3(8x+10)+x | | 2(x×2+4)=12 | | -3x+23.4=4.2 | | 5x+60-20x=-8-7 | | -2(3x-10)+8x=7x+20+7x | | 2(x•2+4)=12 | | 4b-4=6b+8 | | 5+u/8=-5.24 | | 11x+55^2=0 | | 2x+×/2=15 | | 2(x÷2+4)=12 | | -7v+5(v+6)=28 | | -12.2=5.3+w/7 | | 2-(x+5)-(x-2)=-3(x-3) | | 4+14=x+5 | | 5x-11=11x-33 | | 4y+6=(12.5)2.5 | | 2(x+2+4)=12 | | 18x+(-6)=8x+25 | | 11.6=4v-1.2 | | 45x+117=8x+450 | | 4x^2-12x+9=4 |

Equations solver categories